Pakistan at 100 : Environmental Sustainability - World Bank Group (World Bank, Washington, DC, 2019)
This policy note was prepared in parallel to the report Pakistan at 100, Shaping the Future. The report Pakistan at 100 discusses options to accelerate and sustain growth in Pakistan so that the country becomes an upper middle-income country when it turns 100 years old in 2047. This policy note focuses on many areas that are crucial for long-term growth from an environmental sustainability point of view, allowing for an analysis and discussion of some key choices and reform options.